Hacking growth how today's fastest-growing companies drive breakout success - Ellis, Sean; Brown, Morgan (Currency, 2017)
"The definitive playbook by the pioneers of Growth Hacking, one of the hottest business methodologies in Silicon Valley and beyond. It seems hard to believe today, but there was a time when Air Bnb was the best-kept secret known of travel hackers and couch surfers, Pintrest was a niche web site frequented only by bakers and crafters, LinkedIn was an exclusive network for C-suite executives and top-level recruiters, Facebook was My Space's sorry step-brother, and Uber was a scrappy upstart that didn't stand a chance against the Goliath that was New York City Yellow Cabs. So how did these companies grow from these humble beginnings into the powerhouses they are today? Contrary to popular belief, they didn't explode to massive worldwide popularity simply by building a great product then crossing their fingers and hoping it would catch on. There was a studied, carefully implemented methodology behind these companies' extraordinary rise.